Empagliflozin compared with glimepiride in metformin‐treated patients with type 2 diabetes: 208‐week data from a masked randomized controlled trial. Issue 12 (7th August 2018) - Ridderstråle, Martin; Rosenstock, Julio; Andersen, Knut R.; Woerle, Hans J.; Salsali, Afshin; ,
Abstract : Aim: To report results at week 208, including a 104‐week masked extension, of the EMPA‐REG H2H‐SU trial in patients with type 2 diabetes with inadequate glycaemic control on metformin, in which empagliflozin 25 mg given for 104 weeks provided a sustained reduction in glycated haemoglobin (HbA1c) with a small but statistically significant benefit vs glimepiride, sustained reductions in weight and blood pressure, and low risk of hypoglycaemia. Research Design and Methods: Patients with type 2 diabetes and HbA1c 53‐86 mmol/mol (7% to 10%) were randomized to empagliflozin 25 mg or glimepiride 1 to 4 mg for 104 weeks as add‐on to metformin. Patients who completed the randomized treatment period could participate in a 104‐week extension in which they continued the double‐blind treatment allocated at randomization. Results: Of 765 and 780 patients treated with empagliflozin and glimepiride, 576 and 549 patients, respectively, entered the extension period of the study. At week 208, the adjusted mean difference in change from baseline in HbA1c with empagliflozin vs glimepiride was −1.96 mmol/mol, 95% CI −3.57, −0.35 (−0.18%, 95% CI −0.33, −0.03); P = 0.0172. Rescue therapy was given to 23% of patients on empagliflozin and 34% on glimepiride (odds ratio 0.56 [95% CI 0.45, 0.71]; P < 0.0001). Confirmed hypoglycaemic adverse events (plasma glucose ≤3.9 mmol/L and/or requiring assistance) occurred in 3% of patients on empagliflozin and 28% on glimepiride (odds ratio 0.08 [95% CI 0.05, 0.13]; P < 0.0001). Conclusions: In patients with type 2 diabetes, empagliflozin 25 mg as add‐on to metformin for 208 weeks reduced HbA1c with a significantly lower risk of hypoglycaemia and a significantly smaller proportion of patients receiving rescue therapy compared with glimepiride.